Impelementasi Takzir dalam Membentuk Karakter Santri di Pondok Pesantren Miftakhurrosyidin Kabupaten Temanggung Jawa Tengah - Anisatul Ngazizah; Moh. Syafi' (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2021)
This research discusses the implementation of takzir in Islamic boarding school Miftakhurrosyidin, Temanggung Regency. Takzir is a form of punishment that is intended to educate and correct the perpetrator to realize that his actions are prohibited and to then leave and stop it, however some parties think that takzir does not have educational values, is identical to violence and is a form of bullying against students. This study aims to determine the implementation of takzir in Miftakhurrosyidin Islamic boarding school, whether takzir does not have educational values ​​or can it actually shape the character of students. In accordance with the locus, this study uses a descriptive qualitative approach. The results of the study show that: first, takzir is followed up by the security officers gradually and according to the level of violations committed by the students. Second, physical punishment does not endanger the physical condition of the students while non-physical punishment is in the form of punishment which is intended to strive for the intellectual and spiritual development of the students. Third, the students are increasingly qualified in thinking, behaving and embracing fellow friends to jointly achieve success in studying blessed and useful knowledge by not violating the rules at the Islamic boarding school and istikamah carrying out routines at the Islamic boarding school.